Factors related to pain management adequacy in patients receiving palliative care: data from a tertiary hospital in Indonesia (Medical Journal of Indonesia, 2020)
BACKGROUND Adequate pain management must be applied to improve the quality of life, particularly in patients receiving palliative care. Thus, this study aimed to determine the factors related to pain management adequacy in patients receiving palliative care. METHODS This cross-sectional study included all patients sent for consultation to the palliative care team complaining of pain in Cipto Mangunkusumo Hospital, Jakarta, Indonesia from 2016 to 2018. All data such as gender, age, employment status, disease type, primary cancer location, pain intensity, analgesic drug treatment duration, and the presence of anxiety and depression were retrieved from medical records. Pain management adequacy was evaluated using the pain management index. Logistic regression included all variables with p<0.25 related to pain management adequacyin bivariate analysis. RESULTS Out of 175 patients with pain, 85.7% reported having adequate pain management. Pain was more adequately treated in patients with employment (p = 0.001), milder pain intensity (p<0.001), those using opioids (p<0.001), and those who did not experience anxiety (p = 0.05). Factors related to pain management adequacy were opioid use (OR = 3.23, 95% CI = 1.71–6.13) and milder pain (OR = 11.15, 95% CI = 3.89–31.99). CONCLUSIONS Most of the patients received adequate pain management which related to opioid use and milder pain.